"Hey, I Got to Smoke Some Weed": Favorable Perceptions of Marijuana Use Among Non-College-Educated Young Adult Cigarette Smokers. (1st January 2020) - Chen-Sankey, Julia Cen; Jewett, Bambi J.; Orozco, Leah; Duarte, Danielle A.; Dang, Kathleen; Seaman, Elizabeth L.; Choi, Kelvin
Abstract: Introduction: As marijuana legalization progresses in the U.S., this study investigated the perceptions of marijuana use among non-college-educated young adult smokers. Methods: Twelve focus groups were conducted to explore themes related to marijuana and marijuana use among a racially and ethnically diverse sample of 75 young adult smokers (ages 18–29 years) with <4-year college education and <90, 000 annual household income living in the Washington, D.C. metropolitan area. Thematic content analysis was employed to analyze the transcripts. Data collection and analysis took place in 2017 and 2018, respectively. Results: Many participants reported smoking cigarettes to boost and maintain the psychoactive effect ("high") of smoking marijuana; some smoked marijuana to substitute frequent cigarette smoking. Participants generally stated that they believed marijuana smoking was healthier and less addictive than cigarette smoking; many preferred smoking marijuana over cigarettes. Participants also mentioned that cigarette smoking was stigmatized and not socially acceptable but marijuana smoking was "trendy" and "cool." Some reported that they smoked marijuana to cut down on cigarettes, although most were unsuccessful. Racial and ethnic differences in marijuana use were also identified. Discussion: Non-college-educated young adult smokers expressed largely favorable views towards smoking marijuana. Such positive views may lead to prolonged and escalated use of cigarettes and marijuana, resulting in exacerbated adverse health consequence of smoking both products as well as worsened outcomes of cigarette smoking cessation. Evidence-based messages are greatly needed to communicate the harm and risks of marijuana use and marijuana and tobacco co-use among this group.